Good Practices in Implementing the Circular Economy in the Energy Sector - Conversion of Fly Ash into Construction Materials - Całka, Paweł Ł.; Tokarczyk-Dorociak, Katarzyna; Kazak, Jan K. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The support of actions aimed at reducing levels of pollution emissions into the environment requires popularization of good practices, including those involving solutions in the field of the circular economy. These actions are particularly important in sectors of the economy characterized by a high share of total emissions, as their modernization through economies of scale translates into greater environmental benefits.
Keywords: circular economy; energy sector; 6R; recycled materials; value stream mapping